Chemical Composition of Scrophularia lucida and the Effects on Tumor Invasiveness in Vitro - Lewenhofer, Verena; Schweighofer, Lisa; Ledermüller, Tobias; Eichsteininger, Julia; Kählig, Hanspeter; Zehl, Martin; Nguyen, Chi H.; Krupitza, Georg; Özmen, Ali; Krenn, Liselotte (Frontiers in Pharmacology, 2018)
A detannified methanolic extract of Scrophularia lucida L. attenuated the formation of cancer cell-induced circular chemorepellent induced defects (CCIDs) in the lymph endothelial cell barrier, which resemble entry ports for the intravasating tumor into the vasculature as a prerequisite for lymph node metastasis. Therefore, the composition of this extract was studied in an activity-guided approach. Since no data on the secondary metabolites of this plant were available, first phytochemical data were collected in the course of the fractionation of the extract. The study resulted in the identification of fourteen substances, among them very rare iridoids, such as scrovalentinoside or koelzioside, and several flavonoids (e.g. nepitrin and homoplantaginin). One of the latter group, 2“-O-acetyl-homoplantaginin, is a new natural compound. In the most active fraction, the flavonoid hispidulin was identified as major component and the assay of the pure compound confirmed a contribution of hispidulin to the CCID-inhibitory effects of S. lucida. The activity of the two major iridoids in this assay was less as compared to hispidulin.